National Institutes of Health–Funded Anesthesiology Research and Anesthesiology Physician-Scientists: Trends, Promises, and Concerns. (December 2019) - Chandrakantan, Arvind; Adler, Adam C.; Stayer, Stephen; Roth, Steven
Abstract : With a difficult National Institutes of Health (NIH) funding climate, the pipeline of physician-scientists in Anesthesiology is continuing to get smaller with fewer new entrants. This article studies current NIH funding trends and offers potential solutions to continue the historical trend of academic innovation and research that has characterized academic Anesthesiology. Using publicly available data, specifically the NIH REPORTeR and Blue Ridge Institute for Medical Research, we examined NIH trends in funding in academic Anesthesiology departments that have Anesthesiology residency training programs. When adjusted for inflation, median NIH funding of departments of Anesthesiology declined approximately 15% between 2008 and 2017. The majority (55%) of NIH funding to academic Anesthesiology departments, including R01 and K-series grants, went to 10 departments in the United States. This trend has remained relatively constant for the 9-year period we studied (2009–2017). There is an inequitable distribution of NIH funding to Anesthesiology departments. Arguably, this may be a case of the "rich get richer, " but the implications for those who are trying to become or remain NIH-funded investigators are that success may depend, in part, on securing a faculty position in one of these well-funded departments.